A review of public expenditures for nutrition in national government agencies of the Philippines (2017-2019) - Jhanna Uy; Julienne Lechuga; Valerie Gilbert Ulep (Philippine Institute for Development Studies (PIDS), 2022)
Given the persistently high under -5 stunting prevalence in the Philippines, it is important to look at how the country has invested in nutrition interventions to inform priorities for future resource mobilization. Measuring and tracking of nutrition financing are not only critical for transparency and accountability but also to improve resource mobilization and bolster advocacy activities. This rev iew analyzes the level of public spending for nutrition of 19 national government agencies (NGAs) in the Philippines for 2017-2019 including an analysis of patterns of allocation across and within sectors. For this, we used the methodology of the Scaling Up for Nutrition (SUN) Movement to measure public spending on nutrition in select national government agencies (NGAs). [...]
Keywords: 330; nutrition; public expenditure review; Philippines